DEVELOPMENT OF QUALITIES OF ENDURANCE OF THE STUDENT-YOUTH (American Journal of Interdisciplinary Research and Development, 2023)
This article covers theoretical concepts about the quality of endurance and recommendations on the organization of classes in military-academic lyceums and militarized boarding schools on improving the overall endurance qualities of students in the course of classes and post-class training. Endurance, that is, when we pay attention to athlete endurance - this is the ability of the body to resist fatigue during prolonged exercise. Endurance is theoretically divided into two types – general and special endurance, physiologically differentiated into 4.